Falling up the stairs: An exploration of the effects bracket creep on household incomes - Herwig Immervoll (University of Essex, Institute for Social and Economic Research (ISER), 2004)
This paper analyses how inflation-induced erosions of nominally defined amounts built into relevant tax rules (“bracket creep”) alter distributional and revenue-generating properties of income taxes and social insurance contributions. Using a multi-country tax-benefit model, it provides quantitative estimates for Germany, the Netherlands and the UK. In the absence of automatic inflation adjustment mechanisms, effects on individual tax burdens can be substantial even with low inflation. Bracket creep is found to reduce tax progressivity. At the same time, overall tax revenues increase. This second effect more than compensates for the decline in progressivity and leads to an overall increase of relevant redistribution measures. Existing adjustment regimes used in the Netherlands and the UK are successful at preventing large tax burdens changes resulting from inflation-induced nominal income changes.
Keywords: C81; H24; D31; 330; Inflation; Fiscal Drag; Income Tax; Social Insurance Contributions; Income Distribution; European Union; Microsimulation; Steuerinzidenz; Inflation; Steuerbemessung; Steuerprogression; Sozialversicherungsbeitrag; Deutschland; Niederlande; Großbritannien